The Expression of the Short Isoform of Thymic Stromal Lymphopoietin in the Colon Is Regulated by the Nuclear Receptor Peroxisome Proliferator Activated Receptor-Gamma and Is Impaired during Ulcerative Colitis - Martin Mena, Anthony; Langlois, Audrey; Speca, Silvia; Schneider, Lucil; Desreumaux, Pierre; Dubuquoy, Laurent; Bertin, Benjamin (Frontiers in Immunology, 2017)
The etiology of inflammatory bowel diseases remains largely unknown. We previously demonstrated that the expression of the peroxisome proliferator activated receptor-gamma (PPARgamma) is downregulated in colonic epithelial cells of patients with ulcerative colitis (UC). PPARgamma is a nuclear receptor that modulates inflammation. We hypothesized that its deficiency may play a role in the loss of intestinal homeostasis through the control of immunomodulatory factors. We found that thymic stromal lymphopoietin (TSLP), an epithelial cytokine with pleiotropic functions, is regulated by PPARgamm. While this cytokine possesses two isoforms, only the short form (sfTSLP) was regulated by PPARgamma. sfTSLP mRNA expression was decreased both in PPARgamma knock-down Caco2 cells and cells treated with PPARgamma antagonist, whereas PPARgamma agonists induced the expression of sfTSLP in Caco2 and T-84 cells. The response element activated by PPARgamma was identified in the promoter of the sfTSLP gene by chromatin immunoprecipitation and gene reporter assays. The expression of sfTSLP was significantly decreased in the colonic mucosa of UC patients compared to controls and was correlated with PPARgamma expression. Our results identified sfTSLP as a new PPARgamma-target gene and support the hypothesis that, in UC, PPARgamma deficiency in colonic mucosa could play a role in the loss of intestinal tolerance through an impaired sfTSLP expression.